Evaluation of high-oil and high-protein soybean using component pricing. Issue 2 (4th March 2018) - Xing, Xinying; Popp, Michael; Chen, Pengyin; Manjarrez-Sandoval, Pedro; Gbur, Edward
ABSTRACT: Breeding soybean [ Glycine max (L.) Merr] for either increased seed oil and/or protein concentration requires a cost-benefit analysis to determine the economic value of enhancing a particular trait at the potential cost of yield and possible reductions in protein concentration when targeting high oil or sacrificing oil concentration for higher protein. Soybean growers and processors can benefit from such breeding efforts if oil and protein traits are rewarded using component pricing. In this study, promising soybean breeding lines, targeting either oil or protein, were compared to a baseline of commodity soybean cultivars. The analysis showed whether and how much to increase a particular trait considering changes in yield and other valuable traits across a range of soybean, soybean oil, and soybean meal prices. Sensitivity analysis using price years where either soybean oil or soybean meal prices were favored showed that targeting high protein has been more profitable than the pursuit of increased oil concentration regardless of price scenario chosen, as increases in yield and loss of oil concentration favored profitability when protein concentration was enhanced.